The Influence of Research Based Learning Model on Independent Learning and Creative Thinking Skills in Graph Theory - Puput Suriyah; S. T. Budi Waluya; Dwijanto Dwijanto; Isnaini Rosyida (Universitas Negeri Semarang, 2021)
This study aimed to reveal influence of the research-based learning model on independent learning and creative thinking skills of students on graph theory. This research was conducted at the students of Mathematics Education Program IKIP PGRI Bojonegoro for 8 weeks. The data used to measure influence student learning independence was gathered through a questionnaire; and the students’ creative thinking skills and learning outcomes of Research Based Learning Model were measured through a test. It used quantitative method using multiple regression test. Data were analyzed using SPSS 22.00 for windows. The results of the study showed: (1) there was influence between learning independence on learning outcomes Reseach Based Learning model (2) there was influence between creative thinking skill on learning outcomes Reseach Based Learning model, and (3) there was influence between learning independent and creative thinking skill on learning outcomes Reseach Based Learning model which is 72.6%.